How Does Investment Risk Mediate the Effect of Investment Literacy on Online Interest in Investing Among Generation Z? - Wartoyo; Novi Nur Azizah; Rita Kusumadewi (Journal of Social Science and Business Studies, 2024)
This study aims to determine whether or not there is an influence of investment literacy on online  investment interest with investment risk as an intervening variable. The type of research used is case study research with a quantitative approach and uses data collection techniques through questionnaires distributed online. The population in this study is generation Z in Cirebon City  with a sampling technique using probability sampling, namely  with a simple random sampling  method of 155 people, with path analysis using the help of IBM Stastistic SPSS software version 25. The results showed that the level of investment literacy had a positive and significant effect on online investment interest  with a calculation of 12,251 (>1,655) and a significance value of 0,000 (<0.05). Investment risk has a positive and significant effect on online investment interest  with a calculation of 5.377 (>1.655) and a significance value of 0.000 (<0.05). While in the sobel test, it is known that investment risk can mediate the influence of investment literacy on online investment interest  of 4.2353714571305.